AN EMPRICIAL ANALYSIS OF THE DETERMINANTS OF FDI AND THE CAUSAL RELATIONSHIP BETWEEN FDI AND ECONOMIC GROWTH OF THE ECONOMIES OF ASEAN-5 NATIONS - Pandey, Shagun (2020)
Foreign direct investment plays a significant role in the development of emerging economies. This dissertation focuses on identifying key factors that attract FDI to ASEAN-5 countries, which includes Malaysia, Philippines, Singapore, Thailand and Indonesia, as well as determine the causal relationship between FDI and economic growth in the long run. This study utilizes the Autoregressive Distributed Lag Model pioneered by Pesaran et al. (2001) and the Vector Autoregressive Model to identify which factors have a significant long-run impact on the inflows of FDI to the ASEAN-5 countries for the period 1975-2018. Moreover, the Granger Causality method is employed to establish causal relationships between FDI and GDP in all the countries. The empirical results suggest that FDI converges to its long-run equilibrium under both the models. However, the VAR model provides better results as compared to the ARDL model. Consistent with existing literature, government consumption, domestic investment, infrastructure development, trade openness, return on investment and real exchange rates significantly impact the FDI inflows to Malaysia, Indonesia and Philippines under the VAR model. However, infrastructure development in Singapore as well as domestic investment, infrastructure development and real exchange rates in Thailand do not have a significant impact on the FDI inflows to the respective countries. Finally, unidirectional causality flows from GDP to FDI in all the countries except Singapore, which has a feedback relationship.